2003
DOI: 10.1002/art.10986
|View full text |Cite
|
Sign up to set email alerts
|

Daily pain and symptoms in children with polyarticular arthritis

Abstract: Physicians should consider treating pain more aggressively in children with arthritis, in order to preserve function in school and social domains, as well as physical function. Moreover, optimal pain management in children with arthritis should include therapeutic regimens addressing anxiety as well as standard pharmacologic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(185 citation statements)
references
References 48 publications
(61 reference statements)
10
170
1
4
Order By: Relevance
“…Pain in JIA is exacerbated by changes in variables such as stress, coping and mood. Individual differences in anxiety levels have been found to predict greater daily pain and reduced participation in social and school activities in children with JIA (11). Children with JIA coping with higher levels of pain tend to use less positive self-statements and more catastrophizing (ie, engaging in overly negative thinking about pain) (9,(18)(19)(20).…”
Section: Predictors Of Pain In Jiamentioning
confidence: 99%
“…Pain in JIA is exacerbated by changes in variables such as stress, coping and mood. Individual differences in anxiety levels have been found to predict greater daily pain and reduced participation in social and school activities in children with JIA (11). Children with JIA coping with higher levels of pain tend to use less positive self-statements and more catastrophizing (ie, engaging in overly negative thinking about pain) (9,(18)(19)(20).…”
Section: Predictors Of Pain In Jiamentioning
confidence: 99%
“…A procedure similar to other studies (Schanberg, Anthony, Gil, & Maurin, 2003) was followed to enhance and track adherence to the daily diary protocol. Workers were visited at home by the research assistant one or two days prior to the first day of recording for an orientation to the daily work diary and a structured interview about their work and their personality.…”
Section: Procedures and Measurementmentioning
confidence: 99%
“…For example, Schanberg et al found that children with JIA reported having pain an average of 73% of days over a 2-month period, and that 31% reported pain in the severe range (1); Benestad et al found that 82% of children with JIA reported pain lasting from 30 minutes to 24 hours daily (2). Pain has been shown to be a significant predictor of impaired psychosocial function in patients with JIA, e.g., reduced participation in school and social activities (1)(2)(3), and even minimal reduction in pain has been associated with improvements in quality of life in these patients (4). Results from experimental studies have shown that patients with JIA have reduced pain tolerance and pain threshold compared with healthy controls, and that their pain tolerance is inversely associated with their clinical pain report (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Diaries are thought to improve recall of minor pain episodes and reduce possible recall bias, and have thus been proposed to be a more valid method than single or retrospective assessments (1). In addition, we wanted to examine whether pain-specific beliefs and coping strategies of patients with JIA independently predict their reported pain, while controlling for disease activity and relevant demographic variables following the method used by Turner et al (11).…”
Section: Introductionmentioning
confidence: 99%